Mosaic proximal trisomy 13q and regular trisomy 13 in a female patient with long survival: Involvement of an incomplete trisomic rescue and a chromothripsis event - Verónica Fabiola Morán‐Barroso; Alicia Cervantes; María del Refugio Rivera‐Vega; Adriana del Castillo‐Moreno; Alejandra Moreno‐Chacón; Estefanía Mejía‐Cauich; Laura Eréndira Contreras‐Ortiz; Fernando Fernández‐Ramírez (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Trisomy 13 or Patau syndrome has a prevalence of 1:10,000–20,000 and is characterized by microcephaly, microphthalmia, polydactyly, as well as other dysmorphic features and malformations, with a patient survival of 13% in the first year. Trisomy 13 presents either as a free chromosome 13 trisomy or associated with a chromosomal Robertsonian translocation, as partial trisomy affecting proximal or distal 13q regions, and also as a mosaic. Mosaic trisomy 13 shows a highly variable phenotype, displaying from mild to severe affectations. We present a 12‐year‐old Mexican female patient with intellectual disability, dysmorphic features, polymenorrhea, and long survival, whose initial cytogenetic study referred to a small supernumerary marker chromosome. Methods GTG banding karyotype, high‐resolution chromosomal microarray, and fluorescent in situ hybridization analyses were performed in peripheral blood cells. Results Our analyses demonstrated a de novo mosaicism in our patient, constituted by proximal trisomy 13q10‐q14.3 (82%) and free trisomy 13 (18%) cell lines. Her final chromosomal complement is mos 47,XX,+del(13)(q14.3)[25]/47,XX,+13[7].ish del(13)(RB1+)[17]/13q14(RB1x3)[2].arr[GRCh37] 13q11q14.3(19436286_51726415)x3,13q11q34(19436286_115107733)x2‐3 dn. Conclusions The wide spectrum of clinical manifestations observed in our patient mainly results from the proximal trisomy 13q, and her phenotype is modified by the presence of a free trisomy 13 cell line. We propose that her mosaicism probably derived from a trisomic zygote that underwent a failed trisomic rescue associated with chromothripsis, originating the cell line with partial 13q proximal trisomy, whose selective advantage could explain the long survival of our patient.